Unusual Dental Morphology in a Chimpanzee: A Case Report Utilizing Cone-Beam Computed Tomography - Al-Amery, Samah Mohammed; Nambiar, Phrabhakaran; John, Jacob; Purmal, Kathiravan; Ngeow, Wei Cheong; Mohamed, Nor Himazian; Vellayan, Subramaniam (SAGE Publications, 2018)
This case report illustrates the teeth morphology of a chimpanzee and its anatomical variations. A well-preserved skull of a male Pan troglodytes troglodyte chimpanzee was scanned using a cone-beam computed tomography machine. Measurements included tooth and crown height, root length, root canal length and width (posterior teeth), and pulp cavity length (anterior teeth). Nonmetrical parameters included number of canals and foramina per root of every root. Interestingly, the mandibular central incisor was longer than the lateral incisor, and all the mandibular anterior teeth presented with a solitary flame-shaped or conical-calcified structure in their pulp cavity. The premolars are usually dual rooted except for the first maxillary premolar that displayed 3 roots. Other unusual discoveries were the presence of bilateral radicular dens invaginatus in the mandibular first premolars and the possibility of having 2 canals and 2 foramina in the roots of the posterior teeth. The presence of conical stone mineralizations at the pulp cavity and the presence of dens invaginatus were of particular interest.